1997
DOI: 10.1002/etc.5620160701
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and performance evaluation of the continuous algal toxicity test

Abstract: Responses of Selenastrum capricornutum to cadmium in a chemostat are evaluated under various test conditions defined by the nitrogen to phosphorus ratio, phosphate strength, dilution rate, and ethylenediaminetetraacetic acid content. Based on the test results, these parameters were optimized to achieve superior test sensitivity. This continuous system was also modified to allow testing on a weekly basis. The performance of the modified testing technique was evaluated, employing six different metal toxicants. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The dilution rates for these tests were all maintained at D = 0.5 day −1 . The concentration of Na 2 EDTA·2H 2 O was reduced to 30 g/l following our previous approach [17,18]. One may find that the cell density dropped from 4.6 to 2.2 × 10 6 cells/ml as the PO 4 -P content decreased from 0.28 to 0.14 mg/l.…”
Section: Algal Incubation and Testing Conditionsmentioning
confidence: 98%
See 2 more Smart Citations
“…The dilution rates for these tests were all maintained at D = 0.5 day −1 . The concentration of Na 2 EDTA·2H 2 O was reduced to 30 g/l following our previous approach [17,18]. One may find that the cell density dropped from 4.6 to 2.2 × 10 6 cells/ml as the PO 4 -P content decreased from 0.28 to 0.14 mg/l.…”
Section: Algal Incubation and Testing Conditionsmentioning
confidence: 98%
“…The author's previous works have proposed a short-term continuous algal toxicity test technique, whereby algae were grown and tested under nutrient-limited conditions. Toxicity tests employing different metal toxicants revealed that, with respect to both the median effective concentration (EC 50 ) and the no-observed-effect concentration (NOEC), algae cultured in a continuous reactor are more severely inhibited than those cultured by the batch technique [17,18]. Furthermore, batch and continuous techniques were found to depict completely different relationships in relative toxicity [19].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Most phytotoxicity test methods have been designed to use the freshwater alga Selenastrum capricornutum [6], and many suggested modifications have been developed using this species. A continuous culture technique described and compared with batch culture techniques for S. capricornutum [59,60] is reputed to yield superior sensitivity and reproducibility in exposure tests. An in vivo fluorescence technique for measuring chlorophyll a in S. capricornutum was attempted [58], but this study produced inconclusive results.…”
Section: Algaementioning
confidence: 99%
“…Algae growth inhibition test (AGIT) is one of the most used test to assay effluent toxicity [1][2][3], to evaluate water quality [4,5] and for risk assessment 142 V. REGINATTO et al purposes [6]. Considering this wide range of applications it is expected that samples to be assayed could present different physical-chemical characteristics, like, different degree of colouration.…”
Section: Introductionmentioning
confidence: 99%